AN EFFECTIVE WAY TO PRESENT EDUCATIONAL MATERIALS - Siddikov Ilham Melikuzievich (Galaxy International Interdisciplinary Research Journal, 2022)
The article discusses the principles of using elements of infographics as an effective way to present educational materials in the educational process. The idea of the possibilities and advantages of infographics in the provision of educational information is given.